A Review on the Use of Wearable Functional Near‐Infrared Spectroscopy in Naturalistic Environments1. (19th July 2018) - Pinti, Paola; Aichelburg, Clarisse; Gilbert, Sam; Hamilton, Antonia; Hirsch, Joy; Burgess, Paul; Tachtsidis, Ilias
Abstract: The development of novel miniaturized wireless and wearable functional near‐infrared spectroscopy (fNIRS) devices has paved the way for new functional brain imaging that could revolutionize the cognitive research fields. Over the past few decades, several studies have been conducted with conventional fNIRS systems that have demonstrated the suitability of this technology for a wide variety of populations and applications, to investigate both the healthy brain and the diseased brain. However, what makes wearable fNIRS even more appealing is its capability to allow measurements in everyday‐life scenarios that are not possible with other gold‐standard neuroimaging modalities, such as functional magnetic resonance imaging. This could have a huge impact on the way we explore the neural bases and mechanisms underpinning human brain functioning. The aim of this review is to provide an overview of studies conducted with wearable fNIRS in naturalistic settings in the field of cognitive neuroscience. In addition, we present the challenges associated with the use of wearable fNIRS in unrestrained contexts, discussing solutions that will allow accurate inference of functional brain activity. Finally, we provide an overview of the future perspectives in cognitive neuroscience that we believe would benefit the most from the study of wearable fNIRS devices.